KESIAPAN TAMAN KANAK KANAK DI KECAMATAN CIANJUR MENUJU SEKOLAH RAMAH ANAK - Resi Nur Asyifa, - (2020)
This research is motivated by the number of child friendly schools in West Java, especially in Cianjur Regency. Kindergarten as a unit of early childhood education is a good basis for early childhood. The purpose of this research is to study the condition of kindergarten readiness in Cianjur District towards child-friendly schools, this is an important factor to find out how the fulfillment of children's rights is implemented in early childhood education in Cianjur Regency. This research uses quantitative research survey design. Data collection techniques used observation, interviews and documentation with the resource persons, namely the Principal of Kindergarten in Cianjur District as many as 44 participants. Data analysis techniques using descriptive analysis techniques. The results showed that kindergartens in Cianjur sub-district had diverse readiness and more than 59% of kindergartens in Cianjur sub-district according to the category were ready to go to child-friendly schools.